Quality of life in women during and after treatment for breast cancer: a systematic review of qualitative evidence - Devi, M.; Hegney, Desley (University of Adelaide, 2011)
Background: Breast cancer is the most common cancer in women. With increasing numbers of women surviving breast cancer, there is a need to move beyond the traditional ways of evaluating clinical outcomes and include patient-based outcomes such as the quality of life. Objectives: To integrate and summarise the best evidence related to the quality of life of women diagnosed with breast cancer during and up to ten years after treatment for breast cancer. Inclusion criteria: Types of participants: Adult women (over the age of 18 years) diagnosed with breast cancer who are or have received treatment for breast cancer in the last ten years (i.e. surgery, chemotherapy, radiation therapy and/or hormonal therapy). Phenomena of interest: The quality of life of women diagnosed with breast cancer during and up to ten years after treatment. Context: Women with breast cancer from both developed and developing countries. Types of studies: Studies that focused on qualitative data including, but not limited to, designs such as phenomenology, grounded theory and ethnography, action research and feminist research. Search strategy: The search sought to find both published and unpublished studies between 1990 and 2010, limited to the English language. Eleven electronic databases were searched including CINAHL, PubMed, Scopus and PsycArticles. Methodological quality: Methodological quality was assessed independently by two reviewers using a standardised critical appraisal instrument from the Joanna Briggs Institute. Data extraction: Qualitative data were extracted from the included studies using a standardised data extraction tool from the Joanna Briggs Institute.Results: A total of 42 findings from seven qualitative studies were extracted and rated as unequivocal or credible. Eleven categories were produced. Three synthesised findings were generated based on the meta-aggregation of the categories: (1) “effective care for patients will be achieved if clinicians are aware of the impact of breast cancer and its treatment on the physical and psychosocial domains of women’s quality of life”; (2) “for effective patient-centred care, clinicians must be cognisant of the ways breast cancer and its treatment modalities affect social relationships”; (3) “clinicians should be aware that women use religion and spirituality to cope with breast cancer treatment and improve their quality of life”.Conclusions: This review concludes that the breast cancer diagnosis and its treatment can have a significant effect on several domains of women’s quality of life. Healthcare providers caring for patients need to be well informed about each individual woman’s physical and psychosocial concerns and be cognisant that any attempt to offer support must be targeted to meet the specific challenges faced by each individual woman. Implications for practice: Support and guidance could be provided by healthcare providers through the use of counselling services, psycho-education and organisation of support groups. Elements of counselling and psycho-education should include, when appropriate, joint sessions with the woman’s spouse/partner. As spirituality emerged as a coping mechanism, it is important that women be able to nurture their spiritual relationship in an environment which is supportive. Implications for research: The lack of studies within the Asian context indicates that further research is warranted to examine the impact of breast cancer and its treatment on the quality of life of women from diverse multi-ethnic populations. Further research into self-help strategies to improve the psychosocial well-being of women with breast cancer is warranted. It is noted that when faced with adversity, women seek comfort in religion and spirituality and a study into the relationship between spirituality and quality of life, as well as the effect of culture and religion on the quality of life, is warranted.